Application of the Means Ends Analyswas Learning Model to Improve Student Learning Outcomes in Mathematics Subjects in Class V UPT SDN 3 Amparita - Iroki, Iroki; Paramitha, Hary Yati (Jayapangus Press, 2023)
Matematics ability was necessary for now, but the learning process in which it was carried out was not yet directed, so that it affected the student's learning result. Because it was necessary to apply a learning model that was able to overcome this. The aim of this study was to improve the process and results of student learning of mathematics in Class V of UPT SDN 3 Amparita. The research method used was qualitative research with class action research (CAR). The Data collection techniques used were observation, tests, and documentation. The subjects of this study were teachers and students of class V for the 2022–2023 academic year, which consisted of 23 students. The procedure for applying the action consists of planning, implementing, observing, and reflecting. The results of the research obtained were that the first cycle had less qualification, the second cycle had sufficient qualification, and the third cycle had good qualification. So it could be concluded that the application of the Means Ends Analysis learning model can improve the processes and results of student learning of Mathematics in class V of UPT SDN 3 Amparita.